Case report: A novel WASHC5 variant altering mRNA splicing causes spastic paraplegia in a patient - Gao, Shan-Yu; Liu, Yu-Xing; Dong, Yi; Fan, Liang-Liang; Ding, Qi; Liu, Lv (Frontiers in Genetics, 2023)
Background: Hereditary spastic paraplegia (HSP) is a progressive upper-motor neurodegenerative disease. Mutations in the WASHC5 gene are associated with autosomal dominant HSP, spastic paraplegia 8 (SPG8). However, due to the small number of reported cases, the exact mechanism remains unclear. Method: We report a Chinese family with HSP. The proband was referred to our hospital due to restless leg syndrome and insomnia. The preliminary clinical diagnosis of the proband was spastic paraplegia. Whole-exome sequencing (WES) and RNA splicing analysis were conducted to evaluate the genetic cause of the disease in this family. Results: A novel splice-altering variant (c.712–2A>G) in the WASHC5 gene was detected and further verified by RNA splicing analysis and Sanger sequencing. Real-time qPCR analysis showed that the expression of genes involved in the Wiskott–Aldrich syndrome protein and SCAR homolog (WASH) complex and endosomal and lysosomal systems was altered due to this variant. Conclusion: A novel heterozygous splice-altering variant (c.712–2A>G) in the WASHC5 gene was detected in a Chinese family with HSP. Our study provided data for genetic counseling to this family and offered evidence that this splicing variant in the WASHC5 gene is significant in causing HSP.